Anthropology in an Age of Upheaval. Reflections on Environmental Justice in the American Empire of Oil - Bond, David (Antropologia Pubblica, 2024)
This essay describes ongoing efforts to put anthropology to work confronting American Empire in the field of its material operations. St. Croix, US Virgin Islands is home to one of the largest oil refineries in the world. The Hess/Hovensa/Limetree Refinery has long operated in the colonial shadows of state oversight, disregarding local lives and landscapes in the mass manufacture of cheap energy for the United States. Based on ongoing collaboration with local residents on St. Croix, US Virgin Islands in their struggle to hold the refinery to account, this essay reflects on practical lessons learned about the place of anthropology in anti-imperial struggles today (and the necessity of analyzing and acting with that frame). Reflecting on effective tactics of engaged research today, this essay revolves around three areas of anti-imperial interventions: 1) history of the present; 2) connecting the dots; 3) documenting the harm. Together these three component parts worked in concert to build a common platform of insight, outrage, and radical possibility. They also made it possible to effectively insist on immediate remedies to the harm being done while never losing sight of the imperial structure that caused the harm and necessity of uprooting it.